Development Mathematics Learning Device Based Curriculum 2013 on Subject Prism and Pyramidthrough Problem Based Learning - Afdareza, Melva Yola (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This researchaimed to developmathematics learning device that are Lesson Plan (LP) and Students Worksheet (SW) based curriculum 2013 on subjectprism and pyramidthrough problem based learning.This research use development model by Thiagarajan.Development is done through the following steps: (1) define; (2) design; (3) develop; and (4) disseminate. Learning device that had been developed then validated by three validators and revised based on the input from validators. The valid learning device then tested in the small group trial with subjects are ten students. Based on the data analysis obtained that the mathematics learning device are valid with average for LP 3,74 and 3,44 for SW and practical to use by students.